A specific "at risk" profile related to recent stressful life events in euthymic major depressive disorder. (13th April 2021) - Serafini, G.; Gonda, X.; Aguglia, A.; Amerio, A.; Canepa, G.; Geoffroy, P.; Pompili, M.; Amore, M.
Abstract : Introduction: Stressful life events (SLE) may influence the illness course and outcome. Objectives: The present study aimed to characterize socio-demographic and clinical characteristics of euthymic major depressive disorder (MDD) outpatients with SLE relative to those without. Methods: This sample included 628 (mean age=55.1 ± 16.1) currently euthymic MDD outpatients, among them 250 (39.8%) reported SLE and 378 (60.2%) did not. Results: After univariate analyses, outpatients with SLE were most frequently widowed and lived predominantly with friends/others. Furthermore, compared to outpatients without SLE, those with SLE were more likely to have a family history of suicidal behavior, manifested melancholic characteristics and higher Coping Orientation to the Problems Experienced (COPE) positive reinterpretation/growth and less likely to manifest a comorbid panic disorder, residual interepisodic symptoms, have used psychiatric medications, and use current antidepressant medications. After regression analyses, having a family history of suicide (OR=9.697; p=≤.05), history of psychotropic medications use (OR=2.888; p=≤.05), and reduced use of antidepressants (OR=.321; p=.001) were significantly associated with SLE. Mediation analyses demonstrated that the association between current use of antidepressants and SLE was mediated by previous psychiatric medications. Conclusions: Having a family history of suicide, history of psychotropic medications use, and reduced use of antidepressants may confer a specific "at risk" profile related to the enhanced vulnerability to experience SLE. Disclosure: No significant relationships.